Characteristics of the MQ-135 Sensor for Testing Medium Speed Ship Engine Exhaust Gases - Arif Rakhman Suharso; Ario Hendartono; Slamet Supriyadi (Advance Sustainable Science Engineering and Technology, 2024)
International Convention that regulates air pollution caused by shipping activities as is indicated in Annex VI. So far, many ships' exhaust gases still contain a lot of NOx and SOx gases which can damage the air and are one of the contributors to air pollution. The aim of this research is to analyse the use of the MQ-135 sensor as a ship exhaust gas detection sensor connected to an Arduino Uno and a computer. Testing ship exhaust gas was using the medium speed ship's main engine in the engine laboratory of the Indonesian State Maritime Polytechnic. The measuring point was at the end of the exhaust chimney. The measurement variations consisted of low, medium and high engine speed (RPM) of the main engine. The result suggested that the higher the engine RPM, the higher the reading on the serial monitor. The average of measurement results from three measurements concluded that the high RPM is 96, for medium RPM is 81 and low RPM is 66 as displayed on the Arduino IDE serial monitor. From the results of the equipment testing that has been carried out, it can be concluded that the MQ-135 sensor can be used to detect ship exhaust gas from medium ship engine